PRECIPITATION OF IRON IN SILICON - GETTERING TO EXTENDED SURFACE DEFECT SITES - Decoteau, M; Wilshaw, P; Falster, R (1991)
The gettering of Fe to extended surface defect sites, namely surface pits and oxidation induced stacking faults, has been studied. It is found that, for the conditions investigated, gettering of Fe proceeds by generation of an impurity/crystal defect complex, rather than nucleation of FeSi2 precipitates. The crystal defects are found to be b=1/6〈411〉 interstitial dislocation loops normally observed in the presence of Si1 supersaturation. In this case they are associated with the formation of surface holes. TEM investigation of the bounding partials of OISF's showed no observable gettering of Fe but EBIC investigations showed indirect evidence for decoration on an atomic scale.